Electronic band alignment in AlGaN/GaN high electron-mobility transistors investigated using scanning photocurrent microscopy - Kim, Y. C.; Son, B. H.; Jeong, H. Y.; Park, K. H.; Ahn, Y. H. (Current Applied Physics, 2019)
The band alignment in AlGaN/GaN HEMT devices was investigated using scanning photocurrent microscopy (SPCM) with UV and visible light sources. The polarity of the SPCM on the conduction channel exhibited a switching behavior from p-type to n-type response as the gate bias was increased. The flat-band voltage, which was higher than the DC turn-on voltage, indicates that an ohmic metallic contact was formed for electron transport. We obtained the band offset between the conduction band and the metal Fermi level, which yielded a value of 2.1 eV on average.
Keywords: AlGaN/GaN high electron mobility transistors; Conduction channel; Electron transport; Flat-band voltage; Scanning photocurrent microscopies; SPCM; Switching behaviors; UV and visible light; 2DEG; GaN; HEMT; SPCM